Interaction of recombinant Gallus gallus SEPT5 and brain proteins of H5N1-avian influenza virus-infected chickens - Khairat, Jasmine Elanie; Balasubramaniam, Vinod R. M. T.; Othman, Iekhsan; Omar, Abdul Rahman; Syed Hassan, Sharifah (M D P I AG, 2017)
Septin forms a conserved family of cytoskeletal guanosine triphosphate (GTP) binding proteins that have diverse roles in protein scaffolding, vesicle trafficking, and cytokinesis. The involvement of septins in infectious viral disease pathogenesis has been demonstrated by the upregulation of SEPT5 protein and its mRNA in brain tissues of H5N1-infected chickens, thus, providing evidence for the potential importance of this protein in the pathogenesis of neurovirulence caused by the avian influenza virus. In this study, cloning, expression, and purification of Gallus gallus SEPT5 protein was performed in Escherichia coli. The SEPT5 gene was inserted into the pRSETB expression vector, transformed in the E. coli BL21 (DE3) strain and the expression of SEPT5 protein was induced by IPTG. The SEPT5 protein was shown to be authentic as it was able to be pulled down by a commercial anti-SEPT5 antibody in a co-immunoprecipitation assay. In vivo aggregation of the recombinant protein was limited by cultivation at a reduced temperature of 16 °C. Using co-immunoprecipitation techniques, the purified recombinant SEPT5 protein was used to pull down host’s interacting or binding proteins, i.e., proteins of brains of chickens infected with the H5N1 influenza virus. Interacting proteins, such as CRMP2, tubulin proteins, heat-shock proteins and other classes of septins were identified using LCMS/MS. Results from this study suggest that the codon-optimized SEPT5 gene can be efficiently expressed in the E. coli bacterial system producing authentic SEPT5 protein, thus, enabling multiple host’s proteins to interact with the SEPT5 protein.